OXIDATIVE STATUS AND STATE OF ERYTHROCYTE MEMBRANES IN PATIENTS WITH CONTROLLED AND TRUE RESISTANT ARTERIAL HYPERTENSION - Kuchmenko, O.B.; Sukhoveev, O.V.; Matova, O.O.; Sheiko, V.I.; Omelchuk, O.V.; Lebedynets, N.V.; Parhomenko, O.V. (World of Medicine and Biology, 2022)
Today, arterial hypertension is a global health problem in the whole world. The purpose of the study is to assess the oxidative status and the structural condition of erythrocyte membranes in patients with controlled and true resistant arterial hypertension. In patients, a deterioration in the oxidative status in the development of oxidative stress is observed as evidenced by a significant (p
Keywords: controlled and true resistant arterial hypertension; oxidative status; erythrocyte membranes; electron paramagnetic resonance